2018
DOI: 10.1186/s13018-018-0976-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 3D print-assisted surgery for the treatment of pilon fractures: a meta-analysis of randomized controlled trials

Abstract: ObjectiveTo compare the effects of 3D print-assisted surgery and conventional surgery in the treatment of pilon fractures.MethodsPubMed, Embase, Web of Science, CNKI, CBM, and WanFang data were searched until July 2018. Two reviewers selected relevant studies, assessed the quality of studies, and extracted data. For continuous data, a weighted mean difference (WMD) and 95% confidence intervals (CI) were used. For dichotomous data, a relative risk (RR) and 95% CI were calculated as the summary statistics.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…We have designed and manufactured a large number of 3D printouts with their intra-operative application ranging from models for plate contouring to corrective osteotomy guides and jigs for screw placement. With printouts in direct contact with patient tissues, it is important that we are able to assess for the risk of infection [6]. The overall infection rate of 7% was comparable to figures in the literature using traditional surgical techniques.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…We have designed and manufactured a large number of 3D printouts with their intra-operative application ranging from models for plate contouring to corrective osteotomy guides and jigs for screw placement. With printouts in direct contact with patient tissues, it is important that we are able to assess for the risk of infection [6]. The overall infection rate of 7% was comparable to figures in the literature using traditional surgical techniques.…”
Section: Discussionmentioning
confidence: 59%
“…With regards to the benefits of 3D modelling on surgical execution, a meta-analysis compiling studies for pilon fracture management reported that operation time, blood loss, post-operative pain scores, achievement of anatomical fracture reduction, and post-operative function were all improved in comparison to conventional planning [6]. Rates of infection following 3D modelling amongst this cohort were not increased, and have been reported elsewhere to be as high as 16.1% owing to the degree of associated soft tissue trauma, with an average presentation time of 88-days post-op [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diment [13] used a descriptive-analytical method to analyze the application of 3D printing models in clinical elds and proposed that 3D models have effective applications. Bai et al [12] reported in their meta-analysis that 3D print-assisted surgery was better than a conventional surgery in terms of the operation time, blood loss, and good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The applications of 3D printed models have been investigated in many meta-analyses [12][13][14][15]. These meta-analyses were mainly used in the eld of surgery.…”
Section: Introductionmentioning
confidence: 99%